Expression Profile of Human Fc Receptor-Like 1, 2, and 4 Molecules in Peripheral Blood Mononuclear Cells of Patients with Hashimoto’s Thyroiditis and Graves’ Disease - Rostamzadeh, D.; Dabbaghmanesh, M. H.; Shabani, M.; Hosseini, A.; Amirghofran, Z. (Hormone and Metabolic Research, 2015)
Recently identified Fc receptor-like (FCRL) molecules are new members of the immunoglobulin superfamily dominantly expressed by B cells. Although FCRL expression patterns have been studied in normal and malignant cells, their biological functions and roles remain to be clearly identified in humans. Research has particularly focused on FCRL gene polymorphisms in autoimmune diseases, however, their involvement in the pathogenesis of autoimmune diseases is an interesting field for investigation. In the present study, we have investigated the gene expression profiles of FCRL1, 2, and 4 in 2 common thyroid diseases, Hashimoto’s thyroiditis (HT) and Graves’ disease (GD). FCRL1, 2, and 4 expressions were determined in peripheral blood samples of 55 HT patients, 40 GD patients and equal numbers of normal subjects by quantitative real-time PCR. Our results showed downregulation of FCRL1 and upregulation of FCRL2 transcripts in both HT and GD groups compared to healthy counterparts. Overexpression of FCRL4 was observed only in GD patients compared to controls. A significant correlation was observed between all FCRL gene expression levels in HT patients. Only FCRL2 and 4 had a correlation in GD patients. In addition, FCRL1, 2, and 4 gene expressions showed no correlations with the level of anti-thyroid peroxidase antibody (anti-TPO) or anti-thyroglobulin (anti-Tg) antibody from patients’ sera. In conclusion, expressions of activating or inhibitory FCRL1, 2, and 4 showed significant alterations in HT and GD patients compared to healthy subjects.
Keywords: FCRL; gene expression; Graves’ disease; Hashimoto’s thyroiditis; mRNA; real-time PCR